Electromyography-biofeedback for chronic low back pain: A qualitative cohort study. (May 2023) - Sadora, Jason; Vilsmark, Eric; Bashara, Annie; Burton, Dustin; Paschali, Myrella; Pester, Bethany; Curiel, Marie; Edwards, Robert; Lazaridou, Asimina
Abstract: Background and Aims: Surface electromyography-biofeedback (sEMG-BF) may reduce the burden of CLBP by improving physical functioning, sleep, pain catastrophizing, anxiety, and depression. This qualitative study investigated the impact of weekly EMG-BF sessions on adults with CLBP. Methods: Twenty-six individuals with CLBP participated in telephone interviews after completing an 8-week virtual sEMG-BF intervention. Trained interviewers conducted the 10-to-15-minute semi-structured interviews to understand participants' experience with the intervention. Common themes and subthemes were identified and analyzed using MAXQDA 2022 software. Results: Participants were predominantly middle-aged females ( M = 45, range of 19 – 66) who have had exposure to utilizing conventional therapies such as physical therapy, chiropractor, and massage for the treatment of CLBP. This study focused on participants who reported their experience of the main outcome study which included perceived reductions in CLBP symptoms, including pain and stress, and positive effects on self-awareness and sleep. Three overarching themes emerged and were further divided into subthemes: participants' involvement (virtual experience, accessibility of device, and future recommendations) perceived benefits (participants gained awareness, recommendations for future treatment, met expectations, and implementation), and desire for flexibility (obstacles and COVID-19 Impact). No adverse effects were reported by any of the participants within the study. Conclusions: Both physical and psychological improvements were reported by participants following an sEMG-BF intervention. Specific implementation procedures and critical barriers were identified. In particular, the ability to receive care for CLBP during the COVID-19 pandemic was important to participants. Highlights: Twenty-six chronic low back pain participants were assessed for their subjective experience immediately following a virtual eight-week sEMG-BF program. Virtual Electromyographic biofeedback is favorable for many participants due to accessibility. Electromyographic biofeedback can increase perceived reductions in chronic low back pain symptoms, including pain and stress, and positive effects on self-awareness and sleep.